L’activité spermatogénétique saisonnière de Rana iberica Boul. du nord de Portugal - Crespo, E. G. (1971)
Two different types of European wood-frogs can be distinguished according to the physiological characters of their pituitary-sexual cycles. One type has a potentially continual spermatogenesis (v. g. Rana graeca, Rana latastei), the other one has a seasonal periodic process, under genetic control (v. g. Rana temporaria, Rana dalmatina, Rana arvalis). In our work we study another component of the European wood-frogs’ fauna — Rana ibérica Boul. We found that this Iberian anuran has a potentially continual male cycle as the others Mediterranean frogs, Rana graeca and Rana latastei.